2020
DOI: 10.1530/eje-20-0335
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxicosis in patients with COVID-19: the THYRCOV study

Abstract: Objective. This study assessed thyroid function in patients affected by the coronavirus disease-19 (COVID-19), based on the hypothesis that the cytokine storm associated with COVID-19 may influence thyroid function and/or the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may directly act on thyroid cells, such as previously demonstrated for SARS-CoV-1 infection. Design and Methods. This single-center study was retrospective and consisted in evaluating thyroid function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
378
7
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(461 citation statements)
references
References 31 publications
21
378
7
20
Order By: Relevance
“…Thyroid function of patients with COVID-19 can be manifested as thyrotoxicosis or hypothyroidism. The mortality rate of patients with normal TSH was lower than that of patients with abnormal TSH [ 18 ]. The results of another Chinese study showed that TT3 and TSH levels decreased with the severity of COVID-19 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid function of patients with COVID-19 can be manifested as thyrotoxicosis or hypothyroidism. The mortality rate of patients with normal TSH was lower than that of patients with abnormal TSH [ 18 ]. The results of another Chinese study showed that TT3 and TSH levels decreased with the severity of COVID-19 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone is used for treatment of SAT, but PPT can be observed. Recently, Lania, et al reported that 20.2% of patients with COVID-19 infection developed thyrotoxicosis possibly based on systemic immune activation induced by the SARS-CoV-2 infection [17].…”
Section: Discussionmentioning
confidence: 99%
“…Since ORs are co-expressed with the key mediators of SARS-CoV-2 cell entry (i.e.ACE2, TMPRSS2, cathepsin L) it has been postulated that their damage could be involved in sequelae of COVID-19 from other peripheral organs, not excluding the thyroid [54]. Moreover, SARS-CoV-2 could also indirectly affect the thyroid gland, since "hyperactivity of Th1/Th17 immune responses" and "cytokine storm" associated to COVID-19 may trigger and perpetuate the thyroid gland inflammation [42].…”
Section: Thyroid and Covid-19mentioning
confidence: 99%
“…Most of the published studies were a collection of expert opinions and recommendations on the new strategies of care of thyroid patients in the face of COVID-19 transmission risk and health care surge capacity [8,[28][29][30][31][32][33][34]. Instead, only 13 articles explored thyroid function and/or reported new-onset thyroid diseases in patients contracting COVID-19 [7,[35][36][37][38][39][40][41][42][43][44][45][46]. Only two studies investigated the histopathological characteristics of the thyroid gland and viral thyroid tropism from patients who died of severe COVID-19 [47,48].…”
Section: Introductionmentioning
confidence: 99%